#TITLE_ALTERNATIVE# - ANDITA SETIABAKTI (NIM 10201018), RIO
This final project describe physics of particle system used for cloth dynamic simulation. With particle system model, the dynamics of a cloth can be use to develop interactively and visually realistic simulation or animation. Euler and Runge‐Kutta method are the most common used to simulate these kind of particle system model. Euler method has advantage on computation speed but lack on precision, while Runge‐Kutta more precise but has less computation speed than Euler. Verlet method is a numerical method that start widely used for simulating particle system. With these method simulation can be done with speed and high precision.